GERMANY’S LABOUR SHORTAGE: BETWEEN STRUCTURAL PRESSURE AND UNCERTAIN HORIZONS - ANA-CRISTINA BÂLGĂR (Global Economic Observer)
Germany is currently facing a profound labour shortage that transcends sectoral boundaries and reflects deeper demographic and structural transformations. Following a brief post-pandemic rebound, the German economy has entered a phase of stagnation and mild contraction, further intensifying labour market pressures. Persistent shortages, particularly in skilled occupations, point to long-standing imbalances and systemic constraints. This article examines the structural drivers of these imbalances, focusing on demographic ageing, sectoral disparities, and the enduring weaknesses of Germany’s education, vocational training, and labour migration systems. Drawing on recent statistical and institutional data and policy developments, the analysis shows that, despite being targeted, existing measures remain insufficient in both scope and coherence. Structural rigidities and demographic inertia continue to hinder the country’s ability to adjust to long-term labour market shifts. These findings suggest that a more integrated and forward-looking reconfiguration of Germany’s labour model is needed to ensure long-term economic resilience and demographic sustainability.